2016
DOI: 10.1111/sji.12401
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotypic and Functional Features of Human M2 Macrophages Generated Under Low Serum Conditions

Abstract: The phenotypic and functional features of human M2 macrophages, in particular, their immunosuppressive activity, can considerably vary depending on M2 polarizing stimulus. This study was aimed at the investigation of cytokine production and pro-apoptogenic/inhibitory molecule expression in macrophages generated with GM-CSF using either standard conditions (M1) or deficiency of serum/growth factors (M2-LS cells). In contrast to M1, M2-LS cells were characterized by an enhanced content of CD206 + , B7-H1 + , Fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
0
15
0
9
Order By: Relevance
“…According to Sakhno et al's study, B7‐H1 + (PD‐L1)‐ M2 macrophages prohibited allogeneic T cell proliferating activity in mix lymphocyte culture that was associated with the higher numbers of apoptotic T cells through PD‐1/PD‐L1 pathway . To verify in vivo functionality of PD‐L1 + M2 macrophages stimulated by autocrine VEGF, we focused on their immunomodulatory capacity in allogeneic mice model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sakhno et al's study, B7‐H1 + (PD‐L1)‐ M2 macrophages prohibited allogeneic T cell proliferating activity in mix lymphocyte culture that was associated with the higher numbers of apoptotic T cells through PD‐1/PD‐L1 pathway . To verify in vivo functionality of PD‐L1 + M2 macrophages stimulated by autocrine VEGF, we focused on their immunomodulatory capacity in allogeneic mice model.…”
Section: Resultsmentioning
confidence: 99%
“…According to Sakhno et al's study, B7-H1 + (PD-L1)-M2 macrophages prohibited allogeneic T cell proliferating activity in mix lymphocyte culture that was associated with the higher numbers of apoptotic T cells through PD-1/PD-L1 pathway. 16 To verify in vivo functionality of PD-L1 + M2 macrophages stimulated by autocrine VEGF, we focused on their immunomodulatory capacity in allogeneic mice model. Flow cytometry analysis firmly showed that by transplantation of~84% vs 4% PD-L1 + M2 macrophages, the cell frequency of host CD8 + and CD4 + T cells in peripheral blood were significantly reduced 19 days post-transplantation ( Figure 5A,B).…”
Section: Allostimulatory Activity Of Pd-l1 + M2 Macrophages In Vivomentioning
confidence: 99%
“…С помощью МоСа-теста оцениваются когнитивные функции -«зрительно-конструктивные навыки», «называние», «внимание», «речь», «абстрактное мышление», «отсроченное воспроизведение заученных слов», «ориентация в месте и времени». 26 [5,24]. МНК выделяли стандартно из гепаринизированной венозной крови (150-200 мл) пациента и инкубировали (3-5 × 10 6 / мл) в течение 18-24 ч при 37 °С и 5% СО 2 во флаконах (150 см 2 , ТРР) в среде RPMI-1640, содержащей 0,05 mM 2-меркапэтанола, 2 mM пирувата натрия, 0,3 mg/ml L-глютамина, 1% раствора незаменимых аминокислот, 100 μg/ml гентамицина, 2% аутоплазмы и рекомбинантный GM-CSF человека (rhGM-CSF, 50 нг/мл, R&D Systems).…”
Section: материалы и методыunclassified
“…Проведенный нами сравнительный анализ макрофагов 1 и 2 типа показал, что М2 характеризуются более низкой антигенпрезентирующей и провоспалительной активностью и при этом обладают более выраженным регенераторным потенциалом за счет высокого уровня продукции целого комплекса нейротрофических, нейропротективных и ангиогенных факторов [5,24]. М2-макрофаги отличаются более низким уровнем продукции провоспалительных цитокинов (IL-1β, TNFα, IL-6, IL-18) и хемокинов (IL-8, MCP-1), при этом активно секретируют эритропоэтин (ЕРО), а также фактор роста эндотелия сосудов (VEGF), необходимый для ангио/васкулогенеза; инсулиноподобный ростовой фактор-1 (IGF-1), индуцирующий пролиферацию/ дифференцировку нейронов, а также астроцитов и олигодендроцитов; ряд других ростовых факторов (BDNF, EGF, FGF-basic), которые могут повышать выживаемость, усиливать пролиферацию, дифференцировку/деление астроцитов, олигодендроцитов, нейронов и эндотелиальных клеток, а также стимулировать эндогенные, в том числе и нейральные прогениторные, клетки.…”
unclassified
“…Ге-нерируемые макрофаги экспрессировали М2-ассоциированные и проапоптогенные молекулы и по сравнению с М1-клетками обладали сни-женной секрецией провоспалительных цитоки-нов/хемокинов и низкой способностью стиму-лировать пролиферацию аллогенных Т-клеток, но при этом характеризовались высокой про-дукцией ростовых и нейротрофических факто-ров (IGF-1, VEFG, EPO, BDNF, EGF, FGF-basic) [8,69]. Пилотные клинические исследования аутологичных М2-клеток при церебральном инсульте и ДЦП показали, что интратекальное введение М2-клеток безопасно и не индуцирует системной воспалительной реакции.…”
Section: Chernykh Er Et Al черных ер и др Medical Immunology (Runclassified